Implementasi Moderasi Beragama Pada Era MBKM Terhadap Mahasiswa Perguruan Tinggi Agama di Bali - Suwindia, I Gede; Kurnia Wati, Ni Nyoman (Jurnal Penelitian Agama Hindu, 2024)
The aim of the research is to examine the implementation of religious moderation at religious universities, especially Hinduism, for students in the era of independent learning at independent campuses. This research is a type of experimental research using a quantitative approach. The research subjects for the existence of religious moderation in the MBKM era were 350 students from four religious universities in Bali and the object of the research was religious moderation in MBKM. The data obtained in this research was collected using a questionnaire method. Before using the questionnaire, an expert/judge validity test was carried out using the Gregory formula. The item validity test shows that 25 questionnaires are valid with a reliability of 0.81 in the very high category. The data analysis method is quantitative descriptive. The results of research on the implementation of religious moderation in the independent campus era have been very well carried out in religious universities in Bali. This is proven by data from moderation indicators including national commitment, tolerance, non-violence, and accommodating to local culture. The average national commitment data is 26.32 and if this mean is converted into a Liket scale table it is in the very high category. The average tolerance data is 27.45, if converted into a table it is in the very high category. The average anti-violence is 26.91, if this mean is converted into a table it is in the very high category. And the average accommodative to local culture = 30.48, if converted into the very high category. From the four mean results on the moderation indicators above. So it can be concluded that the implementation of religious moderation at religious universities, especially PTKH in the MBKM era, was carried out very well.